APB e-Postgraduate International Colloquium (ePIC) - UiTM, IPSis (Institut Pengajian Siswazah (IPSis), 2023)
The APB e-Postgraduate International Colloquium is an esteemed initiative orchestrated by the APB Postgraduate Centre every semester. It provides a distinguished platform for students to present their research progress, be it preliminary proposals, research findings, literature studies, and more. The recently concluded 4th e-Pic Series, held in a hybrid mode at the APB Shah Alam, saw the participation of 40 outstanding student presentations from across the globe, including China, Indonesia, Pakistan, and Iraq. The program also hosted two eminent guest speakers - Prof Stefanie Pillay from Universiti Malaya, who serves as the external examiner for the LG750 and LG950 programs, and Prof Dr Atta Gebril from the American University in Cairo, a Mou APB partner. In addition to the distinguished speakers, the program was attended by postgraduate students from Shah Alam and branch campuses, language students from local and international universities, as well as APB lecturers. This eclectic mix of participants ensures a vibrant exchange of knowledge, ideas and feedback, making it a highly valuable platform for the students.